2012
DOI: 10.1093/icvts/ivr126
|View full text |Cite
|
Sign up to set email alerts
|

It sometimes happens: late tracheal rupture after total thyroidectomy

Abstract: Thyroidectomy is a safe procedure often performed either for benign or malignant thyroid diseases. Complication rate is low and tracheal injury associated with thyroidectomy is rarely described. The trachea may be perforated or lacerated intraoperatively; nevertheless, damage is usually recognized and directly repaired with reduced patient morbidity. We review a case of a 45-year-old male with a history of non-invasive thyroid cancer who underwent a total thyroidectomy with a tracheal necrosis and a subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…18 Risk factors associated with the tracheal injury occurring during or after thyroidectomy are female gender, benign thyroid diseases, prolonged intubation with high cuff pressure, toxic goiter, excessive use of cautery with increased blood loss intraoperatively, wound infection, tracheomalacia, and postoperative vigorous cough. 19 Capsular dissection technique, the technique of separating the diseased gland from the surrounding pseudocapsule (pre-tracheal fascia), by dissecting along the surface of the true capsule of the thyroid, will avoid important structures and will prevent complications. In this technique nerve is not exposed or traced.…”
Section: Resultsmentioning
confidence: 99%
“…18 Risk factors associated with the tracheal injury occurring during or after thyroidectomy are female gender, benign thyroid diseases, prolonged intubation with high cuff pressure, toxic goiter, excessive use of cautery with increased blood loss intraoperatively, wound infection, tracheomalacia, and postoperative vigorous cough. 19 Capsular dissection technique, the technique of separating the diseased gland from the surrounding pseudocapsule (pre-tracheal fascia), by dissecting along the surface of the true capsule of the thyroid, will avoid important structures and will prevent complications. In this technique nerve is not exposed or traced.…”
Section: Resultsmentioning
confidence: 99%
“…Equipment should be on hand for performing an emergent tracheostomy if necessary. Rapid sequence induction of anaesthesia and orotracheal intubation with placement of the cuff distal to the site of injury is usually sufficient to control the airway [ 13 ]. The management of delayed tracheal rupture after thyroidectomy should not differ from that of any other delayed tracheal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Despite past assumptions that surgical treatment is indicated in all cases, recent studies have identified a subset of patients who could and should be managed conservatively [ 18 , 19 ]. If necessary, surgery must not be delayed [ 13 ]. Potential patient morbidity can include neck abscess, mediastinitis, pneumothorax, cardiac tamponade and tension pneumomediastinum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injury might show itself during surgery or may undergo necrosis in the early postoperative period. Devascularization of the tracheal wall through thermal coagulation injury or necrosis of an ischemic area are the most likely causes [21][22][23]. Although the diagnosis is easy to make, yet the therapeutic approach remains debatable.…”
Section: Discussionmentioning
confidence: 99%